Interval-Valued Proportional Intuitionistic Fuzzy Sets and Their Aggregation Operators - Kahraman, Cengiz; Onar, Sezi Cevik; Oztaysi, Basar; Cebi, Selcuk (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Proportional fuzzy sets ease the determination of membership, nonmembership and hesitancy degrees of the elements in a fuzzy set. In the literature, intuitionistic fuzzy sets, Pythagorean fuzzy sets, picture fuzzy sets and spherical fuzzy sets have been already extended to their proportional equivalents. In this paper, the interval-valued proportional fuzzy set extensions will be developed. In this paper, their arithmetic operations and aggregation operators are defined and a decision making application is presented.
Keywords: Interval-valued sets; Proportional intuitionistic fuzzy sets; Aggregation operators; Computer Science